2000
DOI: 10.1046/j.1525-1438.2000.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Early invasive (FIGO stage IA) carcinoma of the cervix: a clinico-pathologic study of 476 cases

Abstract: The clinical and histologic features of 476 tumors fitting the 1995 FIGO definition of stage IA cervical cancer, treated at a Sydney tertiary referral hospital between 1953 and 1992, are reviewed. Five-year follow-up was complete with a median of 10 years. The diagnosis was increasingly made by histologic examination of colposcopically directed cone biopsy. The majority (88%) of tumors were squamous. The proportion of both younger women ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 80 publications
3
41
2
Order By: Relevance
“…The proportion of patients with lymph node metastases in FIGO IA1 or invasive carcinomas 3 mm or less in depth is negligible, and many authors have concluded that local excision is adequate management [97,121,[126][127][128][129][130][131][132][133]. Nevertheless, some have adopted the presence of LVI, or ''extensive'' LVI, as an exclusion criterion for conservative management [105,110,111,134].…”
Section: Site-specific Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of patients with lymph node metastases in FIGO IA1 or invasive carcinomas 3 mm or less in depth is negligible, and many authors have concluded that local excision is adequate management [97,121,[126][127][128][129][130][131][132][133]. Nevertheless, some have adopted the presence of LVI, or ''extensive'' LVI, as an exclusion criterion for conservative management [105,110,111,134].…”
Section: Site-specific Recommendationsmentioning
confidence: 99%
“…Nevertheless, some have adopted the presence of LVI, or ''extensive'' LVI, as an exclusion criterion for conservative management [105,110,111,134]. In contrast, there is an increased prevalence of both lymph node metastases and recurrence after local excision in FIGO IA2, and many studies conclude that local excision alone is inadequate for this group of patients [39,103,118,126,128,130,[134][135][136][137][138].…”
Section: Site-specific Recommendationsmentioning
confidence: 99%
“…For depth of invasion of < 3 mm, LVSI has been reported in 4.5 -29% of patients, but increasing to 11.1-46.7% for depth of invasion of 3.1-5.0 mm 16) . The incidence of positive nodes in patients with stage I A1 disease has been reported to be 0.5-0.8% 17,18) . The overall incidence of lymph node metastases in patients with depth of invasion of 3-5 mm has been reported as 7.1%, although this varies from 0% to 13.8% 15,[19][20][21][22][23] .…”
Section: Methodsmentioning
confidence: 99%
“…The reported incidence of lymph metastasis in each FIGO stage of cervical cancer is as follows: stage IA1: 0-0.8 %; stage IA2: 0-7.4 %; stage IB: 11.7-23.2 %; stage IIA: 10.0-26.8 %; stage IIB: 35.2-48.6 % (Buckley et al 1996;Cosin et al 1998;Creasman et al 1998;Elliott et al 2000;Hirai et al 2003;Kasamatsu et al 2002;Lee et al 1989Lee et al , 2006Östör and Rome 1994;Poynor et al 2006;van Meurs et al 2009). The lymphatic spread of cervical cancer usually occurs in an orderly fashion from the pelvic lymph nodes, most commonly the obturator or external iliac lymph nodes, to the common iliac lymph nodes, and then the para-aortic lymph nodes (PALN).…”
Section: Lymphatic Spreadmentioning
confidence: 99%